Investigation of Effective Section Reduction in Low Carbon Steel during SMAW Welding - Mushthofa, Malik; Fakhri Pratama Nurfauzi; Astriana Hardawati (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2023)
Welding, with its advantages of expedient execution and reduced weight, is a favored method for structural connections. However, it poses a significant risk, softening the steel and diminishing load-bearing capacity, underscoring the importance of accurate estimation. The need for precision is paramount, as critical infrastructure must remain operational not only during disasters but also during repair and maintenance activities. To address this challenge, this research introduces an approach to estimate the extent of capacity reduction resulting from welding, providing engineers with valuable insights for maintaining these critical systems structural integrity and functionality. The study examined low-carbon steel with various thicknesses, focusing on Heat Affected Zone (HAZ) width calculations and Abaqus simulations. Welding was performed at a speed of 1.67 cm/s with a 5 mm element increment. This research aimed to investigate the impact of welding parameters on low-carbon steel, particularly concerning HAZ measurements. A 4 mm-thick plate generated a 38.73 mm affected zone, while simulations with 5 mm to 12 mm thicknesses produced progressively narrower affected zones. Results demonstrated that steel plate thickness significantly influences the affected zone width, with thicker plates yielding narrower affected zones. The study examined low carbon steel with a 4 mm thickness, focusing on Heat Affected Zone (HAZ) width calculations and Abaqus simulations. Welding was performed at a speed of 1.67 cm/s with a 5 mm element increment. The research aimed to investigate the impact of welding parameters on low carbon steel, particularly concerning HAZ measurements. Results demonstrated that steel plate thickness significantly influences the affected zone width, with thicker plates yielding narrower affected zones. A 4 mm-thick plate generated a 38.73 mm affected zone, while simulations with 5 mm to 12 mm thicknesses produced progressively narrower affected zones.